Protective Response Mechanisms to Heat Stress in Interaction with High [CO2] Conditions in Coffea spp. - Martins, Madlles Q.; Rodrigues, Weverton P.; Fortunato, Ana S.; Leitão, António E.; Rodrigues, Ana P.; Pais, Isabel P.; Martins, Lima D.; Silva, Maria J.; Reboredo, Fernando H.; Partelli, Fábio L.; Campostrini, Eliemar; Tomaz, Marcelo A.; et al. (Frontiers in Plant Science, 2016)
Modelling studies have predicted that coffee crop will be endangered by future global warming, but recent reports highlighted that high [CO2] can mitigate heat impacts on coffee. This work aimed at identifying heat protective mechanisms promoted by CO2 in Coffea arabica (cv. Icatu and IPR108) and C. canephora cv. Conilon CL153. Plants were grown at 25/20 ºC (day/night), under 380 or 700 μL CO2 L-1, and then gradually submitted to 31/25, 37/30 and 42/34 ºC. Relevant heat tolerance up to 37/30 ºC for both [CO2] and all coffee genotypes was observed, likely supported by the maintenance or increase of the pools of several protective molecules (neoxanthin, lutein, carotenes, α-tocopherol, HSP70, raffinose), activities of antioxidant enzymes, such as superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione reductase (GR), catalase (CAT), and the upregulated expression of some genes (ELIP, Chaperonin 20). However, at 42/34 ºC a tolerance threshold was reached, mostly in the 380-plants and Icatu. Adjustments in raffinose, lutein, β-carotene, α-tocopherol and HSP70 pools, and the upregulated expression of genes related to protective (ELIPS, HSP70, Chape 20 and 60) and antioxidant (CAT, CuSOD2, APX Cyt, APX Chl) proteins were largely driven by temperature. However, enhanced [CO2] maintained higher activities of GR (Icatu) and CAT (Icatu and IPR108), kept (or even increased) the Cu,Zn-SOD, APX and CAT activities, and promoted a greater upregulation of those enzyme genes, as well as those related to HSP70, ELIPs, Chaperonins in CL153 and Icatu.. These changes likely favoured the maintenance of reactive oxygen species at controlled levels and contributed to mitigate of photosystem II photoinhibition at the highest temperature. Overall, our results highlighted the important role of enhanced [CO2] on the coffee crop acclimation and sustainability under predicted future global warming scenarios.